2022
DOI: 10.36416/1806-3756/e20210398
|View full text |Cite
|
Sign up to set email alerts
|

Sleep health and the circadian rest-activity pattern four months after COVID-19

Abstract: Objective: To describe the prevalence and severity of sleep disorders and circadian alterations in COVID-19 patients four months after the acute phase of the disease. Methods: This was a cross-sectional observational prospective study of patients with mild COVID-19, moderate COVID-19 (requiring hospitalization but no mechanical ventilation), or severe COVID-19 (with ARDS) four months after the acute phase of the disease. All patients underwent a home sleep apnea test and seven-day wrist actigraphy, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…COVID-19 patients tend to experience fear and anxiety about social isolation procedures, as well as mandatory lockdowns in the acute phase, leading to an increased incidence of sleep disturbances in the population ( 51 53 ). A study reported a higher prevalence of difficulty falling asleep, staying asleep, and getting up early in patients with moderately severe COVID-19 infection, whereas difficulty staying asleep and waking up earlier was experienced in patients with more severe disease ( 54 ). Another study showing that diabetes mellitus was independently associated with sleep disturbances among patients with post COVID-19 conditions showed that the presence of chronic illnesses can also have an impact on the persistence of sleep disturbance ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients tend to experience fear and anxiety about social isolation procedures, as well as mandatory lockdowns in the acute phase, leading to an increased incidence of sleep disturbances in the population ( 51 53 ). A study reported a higher prevalence of difficulty falling asleep, staying asleep, and getting up early in patients with moderately severe COVID-19 infection, whereas difficulty staying asleep and waking up earlier was experienced in patients with more severe disease ( 54 ). Another study showing that diabetes mellitus was independently associated with sleep disturbances among patients with post COVID-19 conditions showed that the presence of chronic illnesses can also have an impact on the persistence of sleep disturbance ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…While sleep disturbances are common and more recently have been attributed to societal restrictions during the COVID-19 pandemic, a systematic review and meta-analysis revealed that over 50% of people who had been infected with SARS-CoV-2 suffered with sleep disturbances ( 142 ). One small study demonstrated significant sleep impairment four months after having COVID-19 with an increased prevalence among those with obstructive sleep apnea ( 143 ). Chronotherapy is an emerging therapeutic in pulmonary and sleep medicine as we understand how the disruption of circadian rhythm affects cells of virally infected organs such as the lung and the immune system ( 144 ).…”
Section: Current State Of Long Covid Management and Potential Therape...mentioning
confidence: 99%
“…The prevalences of e.g., exercise intolerance, fatigue, joint and muscle pain, and mental disorders are high with 60–87% of patients still suffering from these symptoms. Previous research reported a poor sleep quality of post-COVID patients, too [ 53 , 101 , 102 ]. Jarosch, et al [ 53 ] examined sleep quality of post-COVID patients with polysomnography and compared the results with healthy controls.…”
Section: Discussionmentioning
confidence: 99%